Ground effect on the aerodynamics of three-dimensional hovering wings. (25th October 2016) - Lu, H; Lua, K B; Lee, Y J; Lim, T T; Yeo, K S
Abstract: This paper reports the results of combined experimental and numerical studies on the ground effect on a pair of three-dimensional (3D) hovering wings. Parameters investigated include hovering kinematics, wing shapes, and Reynolds numbers ( Re ). The results are consistent with the observation by another study (Gao and Lu, 2008 Phys. Fluids, 20 087101 ) which shows that the cycle-averaged aerodynamic forces generated by two-dimensional (2D) wings in close proximity to the ground can be broadly categorized into three regimes with respect to the ground clearance; force enhancement, force reduction, and force recovery. However, the ground effect on a 3D wing is not as significant as that on a 2D flapping wing reported in (Lu et al 2014 Exp. Fluids, 55 1787 ); this could be attributed to a weaker wake capture effect on 3D wings. Also, unlike a 2D wing, the leading edge vortex (LEV) remains attached on a 3D wing regardless of ground clearance. For all the wing kinematics considered, the three above-mentioned regimes are closely correlated to a non-monotonic trend in the strength of downwash due to the restriction of root and tip vortex formation, and a positional shift of wake vortices. The root vortices in interaction with the ground induce an up-wash in-between the two wings, causing a strong 'fountain effect' (Maeda and Liu, 2013 J. Biomech. Sci. Eng., 8 344 ) that may increase the body lift of insects. The present study further shows that changes in wing planform have insignificant influence on the overall trend of ground effect except for a parallel shift in force magnitude, which is caused mainly by the difference in aspect ratio and leading edge pivot point. On the two Reynolds numbers investigated, the results for the low Re case of 100 do not deviate significantly from those of a higher Re = 5000 except for the difference in force magnitudes, since low Reynolds number generates lower downwash, weaker LEV, and lower rotational circulation. Additionally, lower Re leads to a weaker fountain effect.